Smart Shopper - Θεοδοσίου, Αντωνία (Τμήμα Επικοινωνίας και Σπουδών Διαδικτύου, Σχολή Επικοινωνίας και Μέσων Ενημέρωσης, 2014)
This thesis entitled «Smart Shopper» prepared by Antonia Theodosiou, 8th semester student of the Department of Communication and Internet Studies, Cyprus University of Technology under the supervision of Lecturer Prof. Lambros Lambrinos and was completed in May 2014. Despite the economic crisis that prevails today, media tablets and smartphones are becoming more and more prevalent devices among consumers and the internet is part of their everyday life. Thus, the study will use the Internet and Information and Communication Technologies (ICT) to create a user-friendlyand free software, which encourages the participation of all consumers regardless of age and gender in information efforts when they come to evaluate in terms of price during their decision making process. The aim of the study is to convert software into an "objective media tool " for all consumer products in order to serve the needs and desires of each individual consumer (eg making purchases with the lowest possible cost, saving valuable time , comparing prices ,creating a personalized shopping list, etc.) . The word 'objective' indicates that consumers are looking for what they are really need, so data medium meet real-time needs. It also provides users with multiple options (e.g. see the store located on the map) and rewards program (e.g. acquisition of vouchers). As the thesis is experimental, quantitative methodology used in the waterfall model for system analysis , which serves to understand in an extend consumers’ needs and design the entire system following these needs. Proper system design from the beginning , it is vital in order to avoid unnecessary problems. After practice system integration, software must serve all or at least most consumer needs, otherwise the system will be considered as a failure. The conclusions of the study can not be considered objective, since the implementation of the system is not fully completed due to the time frame of a bachelor degree. However, future studies could apply this system, test it and evaluate it in terms of its usability and effectiveness on customers’ decision making process.
Keywords: Smart Shopper; Information and Communication Technologies; Waterfall Model; Smart Shopper; Τεχνολογίες Πληροφορικής και Επικοινωνίας; Mοντέλο Kαταρράκτη